GaN Schottky Contact on the Pattern Sapphire Substrate with Reducted Threading Dislocation. (8th April 2019) - Lee, Cheng-Che; Chien, Cheng-Yen; Cheng, Wen-I; Yen, Cheng-Wei; Hu, Po-Yuan; Kuan, Chieh-Hsiung
Abstract : AlGaN/GaN heterojunction has the advantage of large critical electric field and high chemical stability, to be applied in the fields of LED, optical device, and high-frequency transistor. GaN is regarded as a good candidate for replacing Silicon. In this work, the pattern sapphire substrate (PSS) technology is used to grow GaN thin film by MOCVD and further to manufacture Al-GaN/GaN Schottky diodes. Raman spectrum and etching pit den-sity (EPD) are used to measure the GaN's film quality. To reduce defect density and improve electrical performance, different pat-tern dimensions are designed in the Schottky diodes. By using our PSS technology, the EPD can be reduced from 3.87x106(cm -2 ) to 1.37x106(cm -2 ) and the Raman spectrum FWHM can be reduced from 2.46(cm -1 ) to 2.33(cm -1 ). Also, the Schottky contact resistiv-ity can be reduced from 0.0657(Ωcm 2 ) to 0.00266(Ωcm 2 ).